PENGARUH KOMUNIKASI INTERPERSONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT HERMINA GALAXY, KOTA BEKASI - Herminayani, Nurona; Nurbaiti, Dewi Nurbaiti (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to determine and analyze the magnitude of the influence of interpersonal communication and work motivation on employee performance at Hermina Galaxy Hospital, Bekasi City. The research method utilizes descriptive analysis with a quantitative approach. The study’s population comprised the employees of Hermina Galaxy Hospital in Bekasi City, with a research sample of 300 individuals determined using the Slovin formula, resulting in a sample size of 75 employees  as  respondents.  The  research  utilized  descriptive  statistics  and  multiple  linear  regression analysis for data analysis. Each respondent was given 38 questions using a Likert Scale and this research used an Instrument Test (validity test and reliability test), classical assumption test ( normality test, multicollinearity test, and heteroscedasticity test), multi-linear regression analysis, hypothesis  test  (T-test, F  test and  coefficient  of  determination)  an  f  test. Meanwhile, data processing uses the SPSS program version 25. The research results show that interpersonal communication partially has a significant effect on performance by 39.9%, work motivation partially has a significant effect on performance by 18.5% and there is a significant influence of interpersonal communication and motivation variables simultaneously at 40.2% and the remaining 59, 8% is influenced by other variables not examined in this study.